Noncompete Covenants: Incentives to Innovate or Impediments to Growth - Samila, Sampsa; Sorenson, Olav (Management Science, 2011)
We find that the enforcement of noncompete clauses significantly impedes entrepreneurship and employment growth. Based on a panel of metropolitan areas in the United States from 1993 to 2002, our results indicate that, relative to states that enforce noncompete covenants, an increase in the local supply of venture capital in states that restrict the scope of these agreements has significantly stronger positive effects on (i) the number of patents, (ii) the number of firm starts, and (iii) employment. We address potential endogeneity in the supply of venture capital by using endowment returns as an instrumental variable. Our results point to a strong interaction between financial intermediation and the legal regime in promoting entrepreneurship and economic growth. This paper was accepted by Gérard P. Cachon, entrepreneurship and innovation.